Pretransplant Intensive Care Unit Management and Selection of Grade 3 Acute‐on‐Chronic Liver Failure Transplant Candidates. Issue 1 (7th October 2021) - Michard, Baptiste; Artzner, Thierry; Deridder, Mathilde; Besch, Camille; Addeo, Pietro; Castelain, Vincent; Guillot, Max; Harlay, Marie‐Line; Herbrecht, Jean‐Etienne; Janssen Langenstein, Ralf; Schenck, Maleka; Bachellier, Philippe; et al.
Abstract : The aim of this study is to report on the liver transplantation (LT) activity and posttransplant outcome, over time, of patients with grade 3 acute‐on‐chronic liver failure (ACLF‐3) in a single transplant center performing a large number of LTs for patients with ACLF‐3. It aims at showing how pre‐LT intensive care unit (ICU) management impacts post‐LT outcomes, in particular through monitoring the transplantation for ACLF‐3 model (TAM) score. A total of 100 patients who had ACLF‐3 at the time of LT between 2007 and 2019 were included retrospectively. The cohort was divided in 2 periods, with 50 patients in each period. There was an increase in the number of patients with ACLF‐3 who received an LT during the course of the study period and significantly higher 1‐year post‐LT survival rates in the second period compared with the first period (86% versus 66%, respectively; P  = 0.02). Interestingly, patients during both periods had similar severity profiles and scores apart from a significantly lower number of patients with TAM scores >2 at the time of LT in the second period compared with the first period (1 [2%] versus 11 [22%], respectively; P  ≤ 0.01). In addition, patients whose clinical condition improved in the ICU (with a TAM score downstaged between admission and LT) had significantly higher post‐LT survival rates than those whose TAM score stayed the same or increased: 88% versus 70%, respectively ( P  = 0.04). This study shows a learning curve in LT for patients with ACLF‐3, with optimized ICU management and patient selection leading to increased numbers of LTs for patients with ACLF‐3 and improved post‐LT outcomes. It also delineates how the TAM score can be used to identify the optimal transplantability window for patients with ACLF‐3.